Reducing food losses in developing countries: Simple technological solutions, complex adoption along supply chains - Vos, Rob (Libreria Editrice Vaticana, 2020)
The global food system is malfunctioning, leaving large segments of the population undernourished or malnourished, and causing large environmental damage. Food losses in the production, processing and marketing parts of the food systems are part of the problem. Food wasting at the retail, household and restaurant levels is a serious problem too. The analyses and calls for action in this volume are motivated by the United Nations Sustainable Development Goal (SDG) No. 12, i.e. Ensuring sustainable consumption and production patterns, and specifically, “By 2030, halve per capita global food waste at the retail and consumer levels and reduce food losses along production and supply chains, including post-harvest losses”. This goal is very much in line with the Encyclical Laudato Si’, where Pope Francis calls for changes to overcome the “throwaway culture”. Food Loss and Waste (FLAW) is a moral issue because of the adverse effects on people and our planet. It is detrimental to the planet due to greenhouse gas emissions and the wasting of the water and land used as inputs, and to people – the poor in particular – whose labor is squandered and whose livelihoods are compromised when FLAW occurs.